2013
DOI: 10.3390/ijms141224064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Larvicidal Activity against Culex pipiens pallens of New Triazole Derivatives of Phrymarolin from Phryma leptostachya L.

Abstract: Twelve new triazole derivatives of Phrymarolin were prepared from Phrymarolin I and the structures of all the derivatives were fully characterized by 1H-NMR, 13C-NMR and MS spectral data analyses. Larvicidal activities against 4rd instar larvae of Culex pipiens pallens of these Phrymarolin analogues were assayed. Although the triazole derivatives of Phrymarolin showed certain larvicidal activity, they showed lower activity than Phrymarolin I. The typical non-natural groups triazole substituents reduced the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous phytochemical investigations showed that this plant is rich in lignans, many of which have a unique oxygenated 3,7-dioxabicyclo[3.3.0]octane skeleton, such as phrymarolin I, II, and haedoxan A [1,10,11,12]. In general, these lignans are considered as the main insecticidal active ingredients in P. leptostachya [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical investigations showed that this plant is rich in lignans, many of which have a unique oxygenated 3,7-dioxabicyclo[3.3.0]octane skeleton, such as phrymarolin I, II, and haedoxan A [1,10,11,12]. In general, these lignans are considered as the main insecticidal active ingredients in P. leptostachya [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4-Triazole rings are typically planar aromatic systems, featuring an extensive chemistry [ 10 , 11 ]. 1,2,4-Triazole derivatives represent one of the most biologically active classes of heterocyclic compounds, and their derivatives are characterized with a broad spectrum of biological activity, including anti-cancer activity [ 12 ], antiparasitic activity [ 13 ], larvicidal activity[ 14 ], antifungal activity [ 15 ], herbicidal activity [ 16 , 17 ], antioxidant activity [ 18 ], cytostatic activity [ 19 ], brassinosteroid biosynthesis inhibitors [ 20 ], antimicrobial activity [ 21 ], and so on. Some compounds had been developed as commercial fungicides or herbicides ( Figure 1 ), such as Triadimefon, Triadimenol, Flusilazole, Flupoxamand, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The herbaceous perennial plant, Phryma leptostachya L., is widely distributed in the Himalayas, temperate Asia and northeast America, and has been traditionally used as a natural insecticide in East Asia [2][3][4][5][6][7]. As part of an ongoing effort to identify potential pesticide molecules derived from natural products it was shown that lignans are the main active components of P. leptostachya, and phrymarolin I is a representative member of the lignans isolated from this plant [5][6][7][8]. In this paper, the synthesis and larvicidal activity of novel derivatives of phrymarolin I against Culex pipiens pallens are described.…”
mentioning
confidence: 99%